Weight Trend among Middle School Student: The Mediating Role of Food Addiction and Commitment to Physical Activity - Ban Lateef Saeed, Arkan Bahlol Naji, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Overweight and obesity kill about 2.8 million adults worldwide a year, and contributes to a host of debilitating chronic illnesses, yet obesity is still not typically a focus of medical student training, or continuing education for physicians. The consequences affect an individual physically, financially, and emotionally. The broader society is affected since obesity threatens national security and public safety by reducing the numbers of military and safety officials who are fit for duty and places a huge burden on the healthcare system. Objective(s): The aim of this study is to determine the mediating role of food addiction and commitment to physical activity. Methodology: The descriptive correlational design has been considered a subtype of correlational research, with its primary purpose being to examine relationships between and among variables and it is referred to occasionally as simple correlational design. The study included a convenience sample of male and females middle school students who agreed to participate in this study. The study subjects were recruited from eight public middle schools. The sample size was determined using G*Power software based on an effect size of 0.25, alpha error probability of 0.05, a power of 0.95, five groups. Thus, the recommended sample size would be 304. Considering an attrition rate of 20%, additional 61 subjects would be required. As such, the recommended sample size would be 365. The final sample size is 380. Results: There is a statistically significant difference in commitment to physical activity between gender groups (p-value = 0.005). While there is no statistically significant difference in commitment to physical activity among grade groups. Conclusion: Male students have greater tendency for food addiction than female students. Male students have greater commitment to physical activity than female students. Recommendations: There is a need for the community health nurses to collaborate with the officials in the Ministry of Health (School Health), mass media, and directorates of education to raise students and school officials’ health awareness of the value of adhering to healthy diet and healthy weight.